Концептуальна основа розвитку інноваційного потенціалу підприємства - Чмельова, Ольга Сергіївна; Татарчук, О. Ю. (НТУ "ХПІ", 2013)
У статті розглянуто теоретичні підходи трактування інноваційного потенціалу, надано структуру інноваційного потенціалу, розкрито основні теоретичні аспекти формування та розвитку інноваційного потенціалу підприємства, доведено взаємозв’язок трудового потенціалу з можливостями інноваційного потенціалу підприємства.

The article defines theoretical approaches to the explanation of an innovative potential, the structure of the innovative potential, has been shown, the main theoretical aspects of formation and development of the venture innovative potential have been offered, the connection of the labour potentialand possibilities of the venture innovative potential has been analyzed.
Keywords: конкурентоздатність; інновації; структура інноваційного потенціалу; трудовий потенціал; формування інноваційного потенціалу; розвиток інноваційного потенціалу; innovate potential; labour potential; structure of the innovative potential; formation of the innovative potential; development of the innovative potential